Estudio de la calidad de vida del grupo de los adultos mayores del barrio de San Vicente de Yaruquí en el período mayo 2015-agosto 2015 - Gómez Vicuña, Evita Rosario (2016)
The aim of this study was to establish, with a multidimensional approach, the state of the quality of life of elderly persons (age>= 60 years), who live in the rural parish of Yaruquí (Pichincha, Ecuador). From May to August, 2015 they were applied by direct interview two questionnaires: CUBRECAVI and a sociodemographic form. The sample was composed by 30 persons, of both sexes with an average age of 75.04 years and they fulfilled the inclusion criteria. There were investigated, 10 components of the quality of life (QoL), 8 major: health, social integration, functional skills, activity and leisure, environmental quality (home conditions), satisfaction with life, education, monthly income, and 2 complementary: use of social and health services and the importance of the components of the quality of life. Results: Education level, economic income and environmental quality, diminish the QoL, while factors that improve positively QoL, were: functional skills and social integration.